Women's participation yields benefits for water management: Insights from village dams in India - Falk, Thomas; Steimanis, Ivo; Bartels, Lara; Duche, Vishwambhar; Vollan, Björn; Meinzen-Dick, Ruth S. (International Food Policy Research Institute, 2025)
Empowering women in decision-making is not just a matter of human rights; it is a key driver of sustainable development. When women's knowledge, perspectives, and priorities are integrated into governance, communities design solutions that are more equitable, inclusive, and durable. When women hold political office, for example, governments tend to allocate more resources to public goods and services such as childcare, education, public health, and foreign aid.